ANALISIS PENERAPAN ELEMEN PROSES PEMBELAJARAN BERDIFERENSIASI DALAM PELAJARAN IPAS DI SD INPRES LILIBA KOTA KUPANG - Dollok, Viki Vikranta Yorhans; Naitili, Cornelia Amanda; Nahak, Roswita Lioba (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
The purpose of this research is to determine the implementation of the Differentiated Learning Process Elements in Science and Technology Lessons at SD Inpres Liliba, Kupang City. The type of research used is qualitative research using a descriptive approach. The data collection techniques used in this research were observation, in-depth interviews and documentation with grade IV teachers, school principals and students at SD Inpres Liliba, Kupang City. The collection instruments in this research are observation sheets, interview guides or question sheets. Data were analyzed using the Miles & Huberman model with a sequence of steps for data collection, data reduction, data verification, data presentation, and drawing conclusions. The validity of the data in this research was carried out using source triangulation, technical triangulation and time triangulation techniques. The results of the research show that the implementation of the differentiated learning process at SD Inpres Liliba, Kupang City is implemented at every grade level (I-VI). Learning activities are going well. This can be seen from the completeness of the elements of the differentiated learning process at each stage carried out by the teacher, including: 1) Planning, which consists of preparing guiding questions and implementing tiered activities that have various levels of challenge and complexity. 2) Implementation, which consists of carrying out discussion activities in class according to students' interests and learning profiles, developing learning activities that vary according to students' learning styles (visual, auditory, kinesthetic), and forming flexible learning groups. 3) Evaluation, using assessment instruments such as skills assessment, attitude assessment, knowledge assessment and learning activity assessment as well as class exhibitions to appreciate students' work.